Pengaruh Penggunaan Pacifier Terhadap Nyeri Pemberian Terapi Intravena Di Rumah Sakit Awal Bros Batam - Indah Purnama Sari; Yulianti Wulandari; Septi Wijayanti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
The neonatal period (0-28 days) experiences enormous changes from life in the womb and undergoes organ maturation in every system. The results of 2017 Indonesian Demographic and Health Survey (IDHS) were the Neonatal Mortality Rate (AKN) of 15 per 1,000 live births. The phenomenon found at Awal Bros Batam Hospital was the number of births 208, in infants who underwent intravenous therapy, infants were not given measures to reduce pain such as using a pacifier. Objective To determine the effect of using a pacifier on the pain of giving intravenous therapy to neonates at Awal Bros Hospital Batam. The research design used a pre-experimental design using one group and pre-test post-test design. The sample of this study was 20 babies who were treated at Awal Bros Batam Hospital and received intravenous therapy and the data were analyzed using the Wilcoxon Sign Rank Test. The results revealed a significant difference, which (p-value 0.000 ≤0.05) indicates a significant difference between the average pain scale before and after the intervention. Increasing information and motivation for nurses regarding the effect of using a pacifier on the pain of giving intravenous therapy to neonates at Awal Bros Hospital, Batam.